Perancangan Website Jasa Titip Sebagai Fasilitator Transaksi Global - Aryanti Nur Anisah; Aminatus Sholikah Putri; Fatimah Nur Alifiah; Mochammad Zulfikar; Rhexy Pasha Dwi Olivia; Achmad Zidan Ramdani; Asmaul Khusna; Ronggo Alit (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
The advancement of technology has transformed the way trade is conducted, with the internet becoming the primary platform for business. E-commerce, or online trading, has opened significant opportunities for both sellers and buyers. Furthermore, online personal shopping services have gained popularity, enabling buyers to obtain goods from abroad or remote areas. However, the use of social media and informal communication limits the ease of finding and trusting personal shoppers. In order to address these challenges, this research introduces the "Jastipin Kuyyy" application as an innovative solution to facilitate personal shopping services. This application allows users to easily view and order products, provide reviews, and track their orders. Additionally, users can request items that are not listed in the application. In the technical discussion, this application is designed using the throwaway prototyping method. The process of analyzing website application requirements and system design involves users, with a focus on key features such as ordering, item requests, and order tracking. The Entity Relationship Diagram (ERD) illustrates the application's database structure, while the website usage flowchart provides an overview of user interactions. The "Jastipin Kuyyy" application aims to enhance convenience, security, and user experience in utilizing personal shopping services. It is expected that this application will serve as an efficient solution for users who wish to shop internationally or make use of personal shopping services, facilitating the broader growth of personal shopping businesses.